Legnica - teatr miasta, teatr miejsca - Sajkiewicz, Violetta (Studia Etnologiczne i Antropologiczne, 2010)
The adaptations of industrial halls, power stations, boiler houses or mines into cultural spaces are almost the obvious thing to do. However, even against the background of more and more numerous initiatives, aiming at the activization of neglected city communities, the activity of Modrzejewska Theatre is unusual. The stage in Legnica, directed by Jacek Głomb since the 1990s, shows real stories in real places consistently inscribing into the trend of the so called local theatre, directed, above all, at the inhabitants of a given place or district. In Legnica, the whole city was the stage. The spectacles were played in the rooms of the former tank factory and barracks, in Mary’s Church, discotheque, at the yard of a store hall and in the hall of a closed textile factory. In the beginning, the exit into the spaces theatrically unaccustomed, served Legnica the purpose of, above all, encouragement of people who had not experienced it before, but, with time, the social issues connected with a revitalization of deserted or neglected city spaces became more and more important. While for many directors the city space is just the background of plays, in Legnica it is their integral element. The theatre goes beyond the borderlines of art and becomes an element of life of a local community. It shapes the image of the place in which it lives, builds the citizenship society, aware of history and tradition, knowing its own place in the contemporary world. A pragmatic attitude o art, inscribed into Dewey’s life rhythm, has brought about a social effect. The theatre has changed unto agora whereas Legnica has become similar to the ancient polis the ultimate sense and aim of which was providing life to the community according to its imagination on happiness and good co operation.